Tools of titans the tactics, routines, and habits of billionaires, icons, and world-class performers - Ferriss, Timothy 1977- (Vermillion, 2016)
"Fitness, money, and wisdom--here are the tools. Over the last two years ... Tim Ferriss has collected the routines and tools of world-class performers around the globe. Now, the distilled notebook of tips and tricks that helped him double his income, flexibility, happiness, and more is available as Tools of Titans"--Page 4 of cover
Originally published in the United States by Houghton Mifflin Harcourt in 2016
Keywords: Körperliche Leistungsfähigkeit; Selbstbewusstsein; Erfolg; Successful people / Interviews; Success; Physical fitness; Wealth; Wisdom; Self-actualization (Psychology); Change (Psychology); Self-realization; Conduct of life; Successful people; Interviews; Ratgeber